P–304 The endometrial preparation protocol does not affect the live-birth-rate after vitrified-warmed euploid single blastocyst transfers: an analysis of 1884 procedures. (6th August 2021) - Petriglia, C; Vaiarelli, A; Cimadomo, D; Gentile, C; Fiorini, F; Sansone, A; Uher, P; Masip, M Aur; Chelo, E; Pellegrini, S; Ubaldi, N; Gennarelli, G; et al.
Abstract: Study question: Is the live-birth-rate (LBR) different when comparing artificial (AC) and modified-natural (M-NC) cycle for endometrial preparation to vitrified-warmed euploid blastocyst transfer? Summary answer: The LBR after vitrified-warmed euploid blastocyst transfer seem independent of the endometrial preparation administered. What is known already: Only the transfer of a competent embryo on a receptive endometrium might result in successful implantation. Three main protocols for endometrial preparation to vitrified-warmed embryo transfer exist: NC, M-NC, and AC. None among them, though, has been shown more appropriate than the others to date, especially since, only in a few studies, the analysis was restricted to single euploid blastocyst transfers to limit the impact of embryonic issues on implantation. In conclusion, no clear consensus exists and the choice is still largely based on menstrual/ovarian cycle characteristics and patient's needs. Study design, size, duration: All first vitrified-warmed single euploid blastocyst transfers performed between April–2013 and March–2020 were included in the analysis. Endometrial preparation was conducted with either an AC (N = 1211) or a M-NC (N = 673). The protocol was chosen based on patients' logistical reasons. The primary outcome was the LBR per transfer. Sub-analyses based on blastocyst quality and day of development were conducted. Birthweight, gestational age, gestational and perinatal issues were secondary outcomes. Participants/materials, setting, methods: AC: oral estradiol-valerate 3-times/day from day2–3 of the cycle until the endometrial thickness reached ≥7mm, then 600 mg/day of micronized progesterone. The transfer was conducted on day6 of progesterone administration. M-NC: an intramuscular dose of 10, 000IU hCG was administrated when the leading follicle was >17 mm and the endometrium was thicker than 7mm and trilaminar, plus 400 mg/day of micronized-progesterone as luteal phase support starting 36–40hr post-hCG. The transfer was conducted on day7 after trigger. Main results and the role of chance: The two groups were similar for maternal age at retrieval (38.0±3.3yr) and transfer (38.3±3.3yr), reproductive history, embryological outcomes of the IVF cycle, body-mass-index, basal hormonal levels, and blastocyst features (Gardner's classification: AA = 73%, AB/BA=11%, BB/AC/CA=8%, CC/BC/CB=8%; day5=48%, day6=47%, day7=5%). The LBR was 46.7% (N = 565/1211) and 49.9% (N = 336/673) after AC and M-NC, respectively, resulting in an odds-ratio 1.14, 95%CI:0.94–1.37. The absence of significant differences was confirmed also when adjusted for blastocyst quality and day of full-development (1.16, 95%CI:0.96–1.41). Among the 565 and 336 deliveries, the birthweight was similar (3290.3±470.7 versus 3251.7±521.5 g, Mann-Whitney-U-test=0.5), the gestational age was similar (38.5±1.7 versus 38.4±1.9 weeks, Mann-Whitney-U-test=0.5). Also, the rates of newborns who were normal (81% versus 82%), large (8% versus 9%), and small (11% versus 9%) for gestational age were similar (Chi-squared-test=0.5). The rates of patients experiencing gestational (6% versus 7%) and/or perinatal issues (3% versus 3%) were also similar (Fisher's-exact-tests=0.4). Limitations, reasons for caution: This is a retrospective study conducted in poor prognosis patients indicated to preimplantation genetic testing for aneuploidies. Future randomized controlled trials and cost-effectiveness analysis are desirable, as well as studies in different patient populations. Lastly, each gestational/perinatal issue shall be analyzed per se (e.g. different placentation disorders). Wider implications of the findings: The absence of clinical and perinatal differences between the two protocols for endometrial preparation supports the adoption, whenever needed, of AC. This approach, in fact, allows a higher flexibility in patients' and daily workload management. Trial registration number: None